OC-016 The Toll-like Receptor Pathway Is Recurrently Mutated In Oesophageal Adenocarcinoma. (9th June 2014) - Fels Elliott, DR; Ross-Innes, CS; Eldridge, MD; Fitzgerald, RC
Abstract : Introduction: The interaction between the oesophageal microbiota and the inflammatory microenvironment in Barrett's carcinogenesis is poorly understood. One of the mechanisms by which microbiota may induce chronic inflammation is by triggering Toll-like receptor (TLR) signalling and activation of nuclear factor kappa B. We aimed to utilise whole genome sequencing (WGS) data to investigate TLR mutations and expression in oesophageal adenocarcinoma (OAC), with a focus on TLR9. Methods: We interrogated the mutational profiles of 66 OAC samples, with matched germline references from each case, which had undergone WGS as part of the oesophageal ICGC study. All mutations were verified using PCR and Sanger sequencing. To further explore TLR9 expression along the Barrett's progression sequence, we performed TLR9 immunohistochemistry on tissue microarray samples including normal squamous oesophagus (N=16), duodenum (N=14), non-dysplastic Barrett's (N=53), low-grade dysplasia (N=13), high-grade dysplasia (N=25) and OAC (N=338). Within the large cohort of OAC samples we binarised the intensity scores (0–1 and 2–3) and examined whether there were any significant differences in relation to clinicopathologic variables (TNM stage, histological grade, lymphovascular invasion, survival). Results: We identified missense mutations in TLR pathway genes in 8/66 (12.1%) of OAC samples, including TLR1 (1.5%), TLR4 (3%), TLR7 (1.5%), TLR9 (3%), MYD88 (1.5%), and TRAF6 (1.5%). TLR9 protein was expressed more highly in Barrett's and OAC than normal oesophageal squamous tissue (p < 0.001). The expression in Barrett's was similar to duodenum, however immunopositivity was increased in OAC (p < 0.05) compared with this control tissue. The staining intensity was generally consistent throughout the Barrett's progression sequence with strong immunopositivity (intensity score 3) in 7.7–14.5% of samples. Within the OAC cohort, there was no significant association between TLR9 expression and any of the clinicopathological variables tested. The only significant difference in survival was observed in a small subset of patients with metastatic disease (N = 14 patients), where median survival was significantly decreased for patients with TLR9 intensity score 2–3 (8 months ± 2.24 (standard error)) compared to patients with TLR9 intensity score 0–1 (18 months ± 6.57), p < 0.05. Conclusion: TLR pathway genes appear to be recurrently mutated in OAC, which given the mutational context and heterogeneity of disease 1 could represent significant involvement of the TLR signalling pathway in Barrett's carcinogenesis. Reference: 1 Dulak AM, et al . Exome and whole-genome sequencing of esophageal adenocarcinoma identifies recurrent driver events and mutational complexity. Nat Genet . 2013 May;45(5):478-86 Disclosure of Interest: None Declared.